BAGAIMANA SUFISME MENYELAMATKAN LINGKUNGAN KITA - Syafiin Mansur; Annisa Solihawati; Indah Rahmawati Octavia Macdalena (ADISAM PUBLISHER, 2026)
The research problem in this article is how Sufism saves our environment. The research method used is a qualitative paradigm with an interpretative-hermeneutic approach based on a Sufi perspective. The results show that the environmental crisis currently gripping the world is not only a scientific and technical issue, but also a profound spiritual crisis. Data on Indonesian deforestation in 2025, which reached 433,751 hectares, an increase of 66%, shows how urgent a paradigm shift in managing nature is. The secular and materialist approaches that have been dominant have proven unable to address the root of the problem, namely the loss of awareness of the unity between humans, nature, and God. Research on the role of Sufism in saving the environment is not only academically relevant but also practically urgent. Amid the global climate crisis and increasing deforestation, Sufism can be a bridge between spiritual beliefs and sustainable ecological action. The inner transformation offered by Sufism can create voluntary and profound behavioral changes. Ultimately, saving the environment through Sufism is not only a technical task, but a form of the highest worship. Preserving nature means preserving God’s kauniyah verses and fulfilling the mandate as a caliph on earth.